2015
DOI: 10.2217/fon.15.26
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Intraoperative Radiation Therapy for Early-Stage Breast Carcinoma

Abstract: Intraoperative radiation therapy (IORT) is a method of accelerated partial breast irradiation developed to replace other longer courses of radiotherapy with a single radiation session administered at the time of breast-conserving surgery. The purpose of this review is to summarize the advantages and disadvantages of breast IORT techniques that are currently available, as well to consider potential alternative techniques for breast IORT or ultra-short course breast radiotherapy. Furthermore, we highlight the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 77 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The TARGIT and ELIOT trials provide evidence that suggests IORT may be an acceptable option in the treatment of early-stage breast cancer, but there are drawbacks to those radiotherapy delivery techniques. The photon technique utilized in the TARGIT trial limits dose delivery to 1 cm beyond the lumpectomy cavity because of a high superficial dose (at the applicator surface) [19,20]. However, there is some evidence that the relative biological effectiveness of superficial photons is higher than other radiation modalities [28], which may mitigate this point somewhat.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The TARGIT and ELIOT trials provide evidence that suggests IORT may be an acceptable option in the treatment of early-stage breast cancer, but there are drawbacks to those radiotherapy delivery techniques. The photon technique utilized in the TARGIT trial limits dose delivery to 1 cm beyond the lumpectomy cavity because of a high superficial dose (at the applicator surface) [19,20]. However, there is some evidence that the relative biological effectiveness of superficial photons is higher than other radiation modalities [28], which may mitigate this point somewhat.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Despite these relatively favorable clinical results, there are several well-recognized limitations to available forms of IORT. Most important are the lack of intraoperative imaging (which can be used for catheter placement confirmation, target delineation, and simulate/optimize radiotherapy delivery) and the poor dosimetry resultant from the physical limitations of low-energy photons [19,20]. We sought to improve upon these technical limitations by devising a novel form of IORT at our institution that incorporates threedimensional treatment planning, image-guidance, and higher prescription dose.…”
Section: Introductionmentioning
confidence: 99%
“…The breast surgeon performed the lumpectomy or reopened the previous lumpectomy site, the multi‐lumen brachytherapy applicator (Contura multilumen balloon, Hologic, Inc., Bedford, MA) was then placed into the surgical bed, and the skin was closed over the applicator . A CT scan was then obtained via an integrated CT‐on‐rails system . The CT‐on‐rails allowed CT scans to be obtained without moving the patient.…”
Section: Methodsmentioning
confidence: 99%
“…8 A CT scan was then obtained via an integrated CT-on-rails system. 9 The CT-on-rails allowed CT scans to be obtained without moving the patient. The CT images were first reviewed by the surgeon to verify appropriate applicator placement.…”
Section: Methodsmentioning
confidence: 99%
“…The targeted intraoperative radiotherapy versus whole breast radiotherapy for breast cancer (TARGIT‐A) trial was a noninferiority trial that randomized 3451 women with breast tumors less than 3 cm in size to receive either IORT or a traditional course of external beam radiotherapy (EBRT). In patients aged 40 years or more with small (T1 and small T2), unifocal, hormone‐receptor positive invasive cancers, the TARGIT trial demonstrated that IORT resulted in a similar five‐year local control to traditional external beam radiation to the whole breast …”
Section: Introductionmentioning
confidence: 99%